Complete mitochondrial genome of Mollitrichosiphum tenuicorpus (Okajima, 1908) (Hemiptera: Aphididae: Greenideinae) - Cailing Li; Liyun Jiang; Gexia Qiao; Jing Chen (Mitochondrial DNA. Part B. Resources, 2021)
Here we report the complete mitochondrial genome of the aphid species Mollitrichosiphum tenuicorpus. The M. tenuicorpus mitogenome is 15,727 bp in length and comprising 37 genes typically present in insect mitogenomes, a control region, and a unique repeat region. All protein-coding genes (PCGs) terminate with TAA or TAG except for cox1, which is terminated with T—. The secondary structure of trnS (AGN) loses the dihydrouridine (DHU) arm, but all the other transfer RNAs show the typical clover-leaf secondary structure. The repeat region between trnE and trnF is 458 bp, with a 217-bp repeat unit repeating 2.11 times. Phylogenetic analysis of the M. tenuicorpus mitogenome using the maximum-likelihood optimality criterion places it in a strongly supported sister position to Eutrichosiphum pasaniae. These data show that mitogenome sequences could be useful in resolving phylogenetic relationships of the Greenideinae.